Habit persistence in assets demand. - Fleissig, Adrian R.; Swofford, James L. (Southern Economic Journal, 2023)
Habit persistence is examined for six asset demand categories using U.S. data and a dynamic forward‐looking model. We find habit persistence is greater for more liquid assets compared to riskier assets and may in part explain low holdings of riskier assets. Cash assets are found to be substitutes with other liquid assets under habit formation. Consistent with portfolio analysis, the riskier asset categories of money market mutual funds and bonds are found to be complements in use. The three more risky asset categories have budget elasticities greater than unity indicating that in the long run consumers are more likely to turn to these assets as their wealth increases.